Pemahaman Implementasi Rencana Strategi Bisnis RS PKU Muhammadiyah Petanahan - Andika Purwita Aji; Heru Kurnianto Tjahjono (Universitas Muhammadiyah Yogyakarta, 2016)
Managers Hospital admit that Strategy planning is important forces management, but this Strategy planning still become problem because some obstacles that faced to manage it well and exact. Basic obstacle relate to human resource obstacle that very determine quality and axact strategy planning.There are some obstacles that make strategy planning doesn’t yet optimal as important forces management that very needed on face change environment that change quickly. Key factor success strategy planning is formation systematic strategy, implementation strategy that effective, and restrain even follow up from Implementation (Brenes, et al.2008). According to view of resource, the resource based view of the firm(RBV), Resource that had Hospital can become source that enable to approximating and implementation that can increase efficiency and effectiveness of Hospital (Barney, 1991). Resource and capability determine factor Hospital strategy and profitability determiner factor Hospital (Grant 1997;Collis&Montgomery, 1998). Kind of Research that used in this Research is Qualitative, Populations are head room Nurse, Midwife and all Components that support data Research.Every staff in Hospital hope in order to business strategy planning Hospital can informed spread all to all staffs Hospital through special seminar because Hospital that qualified become hope and wish all of Hospital Components. Strategy business planning Components Hospital generally has prepared well but doesn’t socialised yet to employee in Muhammadiyah Hospital of Petanahan. Suggestion do socialiszation and Implementation workshop Business planning Strategy Hospital.